Boccaccio's fabliaux : medieval short stories and the function of reversal - Brown, Katherine Adams, 1978- (University Press of Florida, 2014)
Provides a new and provocative interpretation of the relationship between medieval French fabliaux and Boccaccio's Decameron, examining their formal similarities.